Effect of applying the health promotion model in stunting prevention and behavior control in Indonesia - Evi Soviyati; Endang S Sulaeman; Ir Sugihardjo; Budiyanti Wiboworini (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Stunting is a condition of failure to thrive in children, due to chronic malnutrition and recurrent infections. This study aimed to evaluate the effectiveness of implementing the health promotion model in stunting prevention and control behavior. MATERIALS AND METHODS: This cross-sectional quantitative analytic study was conducted using a survey method involving 228 mothers of stunted children in Indonesia. Cluster random sampling was used. Data were collected using a questionnaire with a Likert scale, and then, they were analyzed using univariate analysis, multiple linear regression, and pathway analysis to determine the direct and indirect effects. RESULTS: All respondents were of non-risk age (20-45 years), most had height >150 cm (83.8%), moderate weight (93.4%), multigravida parity (87.3%), middle education (70.2%), unemployed (91.7%), monthly income of less than 1,800,000 rupiahs (89.9%), and exclusive breastfeeding (97.4%). Sanitation, self-efficacy, and social support had a significant effect on stunting prevention and control behavior (P < 0.05). Socioeconomic and sanitation effects through self-efficacy indirectly had a significant positive, while parenting through food or nutritional intake had a significant influence on the stunting incidence (P < 0.05). Variables that had a significant positive effect on stunting prevention and behavior directly were perceived vulnerability, perceived severity, perceived obstacles, self-efficacy, social support, community organizing, and facilitator (P < 0.05). Parenting through the health of diarrhea or acute respiratory infection (ARI) had no significant positive effect on the stunting incidence (P = 0.121). CONCLUSION: Almost all variables have a significant direct and indirect effect on stunting prevention and control behavior, as well as the stunting incidence, except parenting through the health of diarrhea or ARI.